Identification of target areas for deep brain stimulation in human basal ganglia substructures based on median nerve sensory evoked potential criteria. Issue 8 (21st July 2003) - Klostermann, F; Vesper, J; Curio, G
Abstract : Objective: In the interventional treatment of movement disorders, the thalamic ventral intermediate nucleus (VIM) and the subthalamic nucleus (STN) are the most relevant electrode targets for deep brain stimulation (DBS). This study tested the value of somatosensory evoked potentials (SEP) for the functional identification of VIM and STN. Methods: Median nerve SEP were recorded from the final stimulation electrodes targeted at STN and VIM. Throughout the stereotactic procedure SEP were recorded during short electrode stops above STN/VIM and within the presumed target areas. After digital filtering, high and low frequency SEP components were analysed separately to parameterise both the 1000 Hz SEP burst and low frequency (<100 Hz) components. Results: SEP recorded in the VIM target region could unequivocally be distinguished from SEP recorded in STN. The 1000 Hz burst signal was significantly larger in VIM than in STN without any overlap of amplitude values. In the low frequency band, a primary high amplitude negativity was obtained in VIM, contrasting with a low amplitude positivity in STN. SEP waveshapes in recordings above target positions resembled SEP obtained in STN. When entering VIM, a sharp amplitude increase was observed over a few millimetres only. Conclusions: Based on SEP criteria, the VIM target but not the STN region can be identified by typical SEP configuration changes, when penetrating the target zone. The approach is independent of the patient's cooperation and vigilance and therefore feasible in general anaesthesia. It provides an easy, reliable, and robust tool for the final assessment of electrode positions at the last instance during electrode implantation when eventual electrode revisions can easily be performed.